Efektivitas Penggunaan Media Pembelajaran Blooket dalam Meningkatkan Motivasi Belajar Siswa pada Pelajaran IPAS di Kelas V SD Negeri 1 Bayuning - Fitri, Ade Amelia; Usamah, Asep (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to determine the effectiveness of the use of blooket learning media in increasing student learning motivation in science lessons in grade V of SDN 1 Bayuning. The research method used is a quantitative pre-experiment method. Sampling in this study used a total sampling technique. The population in this study were all grade V students of SD Negeri 1 Bayuning. Data collection techniques used questionnaires, observations, interviews, and documentation. The results showed that the average pretest score was 60% and the average posttest score was 80%. This study used analysis prerequisite tests, namely normality tests, hypothesis tests, and N-Gain tests with the help of the SPSS 25 program. From the results of normality in the posttest, Sig = 0.221 (0.221 ≥ 0.05) was obtained, and the average pretest score was Sig = 0.737 (0.737 ≥ 0.05), this indicates a normally distributed normality test. Hypothesis testing with testing criteria if the Sig value. (2-tailed) < 0.05, then Ho is rejected and Ha is accepted with a significance level = 0.05, a value of 0.000 is obtained so that it can be concluded that Ho is rejected and Ha is accepted. And the N-Gain Score test is 0.7225 which is categorized as high, the N-Gain percent test is 72.24 which is categorized as quite effective. This shows that the use of blocket learning media can increase student learning motivation.